Perceived benefits and barriers and self-efficacy affecting the attendance of health education programs among uninsured primary care patients. (December 2016) - Kamimura, Akiko; Nourian, Maziar M.; Jess, Allison; Chernenko, Alla; Assasnik, Nushean; Ashby, Jeanie
Highlights: Cues to action in attending health education programs vary among uninsured patients. Self-efficacy increases perceived benefits for physical activity. Self-efficacy decreases perceived barriers for physical activity. Self-efficacy increases perceived benefits and barriers for healthy food choice. Attending health education programs decreases perceive benefits. Abstract: Lifestyle interventions have shown to be effective in improving health status, health behaviors, and self-efficacy. However, recruiting participants to health education programs and ensuring the continuity of health education for underserved populations is often challenging. The goals of this study are: to describe the attendance of health education programs; to identify stages of change to a healthy lifestyle; to determine cues to action; and to specify factors affecting perceived benefits and barriers to healthy food choices and physical activity among uninsured primary care patients. Uninsured primary care patients utilizing a free clinic (N = 621) completed a self-administered survey from September to December of 2015. US born English speakers, non-US born English speakers, and Spanish speakers reported different kinds of cues to action in attending health education programs. While self-efficacy increases perceived benefits and decreases perceived barriers for physical activity, it increases both perceived benefits and perceived barriers for healthy food choices. The participants who had attended health education programs did not believe that there were benefits for healthy food choices and physical activity. This study adds to the body of literature on health education for underserved populations.